2009
DOI: 10.1080/10934520802539715
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of anaerobic degradation of screened dairy manure by upflow fixed bed digesters: Effect of natural zeolite addition

Abstract: The effect of the hydraulic retention time (HRT) on the performance of two up-flow anaerobic fixed bed digesters (UFAFBDs) packed with waste tire rubber (D1) and waste tire rubber and zeolite (D2) as micro-organism immobilization supports was studied. It was found that a first-order kinetic model described well the experimental results obtained. The kinetic constants for COD, BOD5, total solids (TS) and volatile solids (VS) removal were determined to be higher in digester D2 than in digester D1 or control. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…During bioreactor operation, the population density of SRB increased approximately 5 times from 5 days to 9 days operation. This raising altered of cross-feeding, co-metabolism, interspecies hydrogen and proton transfer between SRB cells [36][37]. Furthermore, its condition may further stimulate the growth of micro colonies which effect on the increasing of their activity for removing sulphate and manganese.…”
Section: Characteristics Of Developed Srb Biofilms Populationmentioning
confidence: 99%
“…During bioreactor operation, the population density of SRB increased approximately 5 times from 5 days to 9 days operation. This raising altered of cross-feeding, co-metabolism, interspecies hydrogen and proton transfer between SRB cells [36][37]. Furthermore, its condition may further stimulate the growth of micro colonies which effect on the increasing of their activity for removing sulphate and manganese.…”
Section: Characteristics Of Developed Srb Biofilms Populationmentioning
confidence: 99%
“…The investigation showed that the growth yield (Y G ), specific biomass decay (b), maximum specific biomass growth rate (μ max ), saturation constant (K s ) and critical retention time (Θ c ) were in the range of 0.990 g VSS g Fuzzato et al [26] used simplified first-order kinetics for modeling a mesophilic anaerobic sequencing batch biofilm reactor (ASBBR) treating lipid-rich wastewater. Nikolaeva et al [40] also observed that a first-order kinetic model described the experimental results obtained for the upflow fixed bed digesters treating dairy manure well. In addition, they also concluded that the first-order model was adequate for assessing the effect of HRT on the removal efficiency and methane production.…”
Section: Modeling Advancesmentioning
confidence: 86%
“…The upflow fixed bed reactors or upflow anaerobic filter (UAF) is one of the earlier designs, and its characteristics are well defined [3,22,40]. The UAF is a relatively simple technology; and in engineering terms, it is not as complex as fluidized bed reactors, and in biological terms, it does not require the formation of a granular sludge, a prerequisite for the UASB reactor, which is usually very difficult to maintain.…”
Section: Upflow Fixed Bed Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed by Wilkie et al (2004), flushed dairy manure poses challenges to conventional high temperature anaerobic digesters because of the large volume of flushing water that must be heated. To address this issue, fixed-film digesters with submerged high specific surface area media were introduced to retain active biomass through bacterial attachment (Nikolaeva et al, 2009;Umana et al, 2008;Vartak et al, 1996;Wilkie et al, 2004). Nevertheless, fixed-film was classified as an inappropriate process for dairy manure anaerobic digestion due to its vulnerability to media clogging (Burke, 2001).…”
Section: Introductionmentioning
confidence: 99%